Comparación del nivel de conocimiento sobre su enfermedad en pacientes diabéticos tipo 2 con y sin complicaciones - Lizarzaburu Abanto, Ybis Amparo (2017)
Diabetes mellitus (DM) represents a heavy burden for the patient and society. Most of the direct costs of DM come from its complications, which are possible to reduce, delay and to prevent, in some cases. Objective: Compare the level of disease’s knowledge in type 2 diabetic patients with and without complications. Materials and methods: Cross-sectional observational study. Between December 2016 and February 2017, 160 patients (80 diabetic patients with complications and 80 diabetic patients without complications) were interviewed at Medicine outpatient office at Hospital Belen de Trujillo. Results: 69 male patients (43.12%) and 91 female patients (56.88%) were studied, with a mean age of 59.45 ± 12.74 years. The level of knowledge for both groups of patients (with complications and without complications) was "intermediate", not finding a significant difference in the level of knowledge between these two groups. Conclusion: There is no significant difference between the level of knowledge about diabetes in type 2 diabetic patients with complications and without complications